Roads to Music Sociology - Smudits, Alfred; SpringerLink (Online service) (Wiesbaden : Springer Fachmedien Wiesbaden : Imprint: Springer VS, 2019)
Music sociology occupies a special position in the social and cultural sciences. The terminology alone - in German it is 'Musiksoziologie' and not 'Soziologie der Musik' - indicates many possible approaches: Is 'music sociology' a subdiscipline within sociology or musicology? Or is it a discipline on its own, espousing significant differences from sociology and musicology alike? On the occasion of its 50th anniversary, the Department of Music Sociology at the mdw - University of Music and Performing Arts Vienna - probably the only one in the world to bear the name as a separate department - decided to clarify the state of music sociology. Some of the world's most prominent representatives of the discipline were invited to participate in this project and present their own viewpoints on the various approaches to music sociology. Their contributions address the particular research objects of music sociology (institutions of musical life; production, distribution and consumption of music; music-making; 'works', genres and repertoires; etc.) as well as the different methods of research (stock-taking, surveys, interviews, music analysis, biographical research, etc.). Contents with contributions by Alfred Smudits, Peter J. Martin, Antoine Hennion, Marie Buscatto, Motti Regev, Howard S. Becker, Tia DeNora and Christian Kaden Target Groups Students and lecturers in sociology, social sciences and musicology. The Editor Prof. Dr. Alfred Smudits is head of the Department of Music Sociology at the University of Music and Performing Arts Vienna.
Introduction -- Musicology, Sociology and Digitisation -- From Mediation to Pragmatism: making sociology sensitive again to the value of things?- "Exploring Gender in Music ... to Better Grasp Musical Work" -- Musical Cosmopolitanism, Bodies and Aesthetic Cultures -- Musical Language -- The Unsung Work of Music Sociology? -- Music Sociology in the GDR: under conditions of political dictatorship, despite of political dictatorship.
Keywords: Culture; Mass media; Knowledge, Sociology of; Sociology of Culture; Media Sociology; Sociology of Knowledge and Discourse